The Impact Of Customer Relatonship Management (CRM) Towards E-Business Strategy - Raslan, Umi Kalsoom (2005)
In order to introduce the product or services they need the promotion and also the customer service center. The main factor is to go close to customer and know what they want and what they need. CRM practiced by face-to-face approach, call center and more towards personal contact. However based on these drastic changes of the business world, CRM also would also forced to change to another approach.